Combined association of cardiorespiratory fitness and family history of hypertension on the incidence of hypertension: a long-term cohort study of Japanese males. Issue 12 (December 2018) - Gando, Yuko; Sawada, Susumu; Kawakami, Ryoko; Momma, Haruki; Shimada, Kazunori; Fukunaka, Yasushi; Okamoto, Takashi; Tsukamoto, Koji; Miyachi, Motohiko; Lee, I-Min; Blair, Steven
Abstract Family history of hypertension (FH) is a nonmodifiable risk factor for hypertension. However, cardiorespiratory fitness (CRF) is a modifiable risk factor and might be important for preventing hypertension in both people with and without FH. The purpose of this study was to investigate the combined association of CRF and FH on the incidence of hypertension in normotensive male Japanese workers. A total of 6890 workers were included in this study. CRF was determined using a submaximal exercise test. A self-reported questionnaire was used to determine FH. Six groups were established, combining the two groups with and without FH (Yes, No) and the three CRF groups (Low, Moderate, High). The incidence of hypertension, defined as systolic blood pressure of ≥140 mmHg or diastolic blood pressure of ≥90 mmHg, or self-reported physician-diagnosed hypertension was evaluated. During the observation period of 101, 212 man-years (median 17 years, minimum 1 year, maximum 23 years), 2210 workers developed hypertension. There were 3860 participants who had FH (56%). Compared with the Yes-Low CRF group, the HRs (95% CI) for hypertension were 66% lower in the No-High CRF group (0.34 [0.28–0.40]), 47% lower in the No-Low CRF group (0.53 [0.46–0.61]), and 24% lower in the Yes-High CRF group (0.76 [0.67–0.86]). FH and CRF did not show a significant interaction (p for interaction = 0.181). The combination of FH and CRF showed a clear association with the risk of incident hypertension, and moderate to high levels of CRF might be equally beneficial for preventing hypertension for both people with and without FH.